Civic engagement in an informal settlement: Between the devil and deep blue sea - Okten, Ayse Nur; Inal-Cekic, Tuba; Kozaman, Senem (ELSEVIER SCI LTD, 2021)
Recent discussions and empirical studies on civic engagement suggest that participatory planning efforts have to be differentiated at the local level. This paper conforms to the argument of the local context of decision for engaging and focuses on a multi-scale framework relating macro policy decisions and official practices to individual dilemmas. The emphasis is on three elements of the local context: the legacy of informality policies, ambiguities resulting from local government?s planning practices, and citizens? perception of the local situation. The paper aims to show that, in an informal settlement, these local factors create a dilemma for the residents and make them reluctant to engage. The discussion in the paper is based on our research in the neighborhood Okmeydan?, in Istanbul. Our observations with quantitative and qualitative techniques showed that low levels of engagement with a redevelopment project in an informal settlement could be attributed, among other factors, to citizens? dilemma. The residents find themselves in a perplexing situation. They perceive the project as a chance to achieve improvement in their quality of life but, at the same time, as a threat to their existence due to the risks of gentrification and inequity.
Keywords: Informal settlements; Civic engagement; citizens? engagement; Urban redevelopment; Participation; Okmeydan?; Istanbul; COMMUNITY PARTICIPATION; PLACE ATTACHMENT; URBAN; DISPLACEMENT; CITIZENS; PROJECTS; TURKEY; Urban Studies